Those tiny little things that run the world - Kaunisto Kari Mikael (Finland, 2026)
What has the study of dragonflies’ gut bacteria to do with human well-being? For a researcher, the link is clear: the gut microbiota of humans and insects share many similarities, so the results of insect research may also advance the research of human gut microbiota. As it is known that human intestinal flora may be associated with diabetes and other diseases, any new knowledge in this area is valuable.